Bipolar Radiofrequency as an Adjunct to Face and Body Contouring: A 745-Patient Clinical Experience. (3rd January 2021) - Cook, Jonathan; DiBernardo, Barry E; Pozner, Jason N
Abstract: Background: Radiofrequency (RF) technology has ushered in a new paradigm in body contouring for patients with mild to moderate skin laxity who desire fat removal without exacerbating skin laxity issues. A bipolar internal RF device, used as an adjunct to liposuction, has been found to be simpler and more accurate than previous technologies. Objectives: The aim of this study was to review the authors' clinical experience with bipolar RF-assisted liposuction (RFAL). Methods: We conducted a review of our large experience with bipolar RFAL, evaluating the nuances from appropriate patient selection and specific treatment areas. The review covered 745 patients treated from January 2017 to January 2020 at 2 centers. A retrospective chart review was performed of the first and last 50 patients treated at each center (for a total of 100 patients in each group) to assess trends in outcomes and adverse events. Results: Results were generally excellent from physician evaluation, and overall patient satisfaction was high (96%). The two most common adverse events were temporary swelling (9%) and nodules (8.5%). Selected examples of a variety of cases are reviewed. Conclusions: The ability to tighten skin with a minimally invasive tool adds much to the contemporary approach to the body-contouring patient with skin laxity. Adverse events were minimal and greatly decreased after an initial short learning curve. Bipolar RFAL is a strong addition to our surgical armamentarium and has become an essential tool for our practices. Level of Evidence: 4: